2021
DOI: 10.3389/fonc.2021.615568
|View full text |Cite
|
Sign up to set email alerts
|

Huaier Extract Inhibits Prostate Cancer Growth via Targeting AR/AR-V7 Pathway

Abstract: The androgen receptor (AR) plays a pivotal role in prostatic carcinogenesis, and it also affects the transition from hormone sensitive prostate cancer (HSPC) to castration-resistant prostate cancer (CRPC). Particularly, the persistent activation of the androgen receptor and the appearance of androgen receptor splicing variant 7 (AR-V7), could partly explain the failure of androgen deprivation therapy (ADT). In the present study, we reported that huaier extract, derived from officinal fungi, has potent antiprol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Huaier granule has broad-spectrum anticancer effects reflected in cancer types and enhancing efficacy of anticancer therapies. Except for above cancer types, many experimental studies have also shown its anticancer effect in other solid tumors including lung cancer, 22 cervical cancer, 23 renal cancer, 24 prostate cancer, 25 and cholangiocarcinoma 26 by various classic anticancer signaling pathways. 27 In addition, from this overview, we know that HG can enhance the efficacy of many anticancer therapies such as TACE, chemotherapy, radiotherapy, molecular targeted therapy, surgical resection, radiofrequency ablation to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…Huaier granule has broad-spectrum anticancer effects reflected in cancer types and enhancing efficacy of anticancer therapies. Except for above cancer types, many experimental studies have also shown its anticancer effect in other solid tumors including lung cancer, 22 cervical cancer, 23 renal cancer, 24 prostate cancer, 25 and cholangiocarcinoma 26 by various classic anticancer signaling pathways. 27 In addition, from this overview, we know that HG can enhance the efficacy of many anticancer therapies such as TACE, chemotherapy, radiotherapy, molecular targeted therapy, surgical resection, radiofrequency ablation to varying degrees.…”
Section: Discussionmentioning
confidence: 99%
“…The TCM Huaier ( Trametes robiniophila Murr.) has been used in the clinical treatment of various tumors, including gastric cancer [ 24 26 ]. At present, Huaier is clinically applied mainly as a water extract.…”
Section: Discussionmentioning
confidence: 99%
“…CRPC is a life-threatening PCa and studies have reported that CRPC may be ameliorated by the use of medicines, such as niclosamide ( Parikh et al, 2021 ) and huaier extract ( Liu et al, 2021 ). However, the active components and signaling pathways involved in treatment remain unknown.…”
Section: Discussionmentioning
confidence: 99%